Determinan Faktor Implementasi Sistem Informasi Manajemen Rumah Sakit - Lina Alfiyani; Anindita Hasniati Rahmah; Eny Pemilu Kusparlina; Asmirati Yakob; Widya Kaharani Putri; Noor Alis Setiyadi; Kristofora Karolina Kewa; Nur Kasihana (Jurnal Anestesi, 2026)
The Hospital Management Information System (HMIS) is an integrated information system used to support hospital service delivery and management processes by providing accurate, rapid, and timely information. Although HMIS has been implemented in various hospitals, there are still obstacles that prevent its optimal utilization. Various factors related to service quality and human resources are suspected to influence user satisfaction with the implementation of SIMRS. This study aims to analyze the factors influencing user satisfaction with the implementation of SIMRS. The study employs a quantitative approach with a cross-sectional design. Data analysis was conducted using logistic regression to identify variables influencing the Community Satisfaction Indeks (IKM). The results indicate that information quality, service requirements, service procedures, service time, cost, service products, staff competence, implementation conditions, complaint services, and complaint handling significantly influence SIMRS user satisfaction (p<0.05). The factors with the greatest influence are complaint handling and complaint services. This study concludes that improving service quality, staff competence, and responsiveness to user complaints is necessary to support the successful implementation of SIMRS and enhance user satisfaction.